Short-term functional outcomes of partial meniscectomy among middle-aged patients - Husain, Akhtar; Ahmad, Saeed; Khan, FarmanUllah (ADVANCES IN BASIC MEDICAL SCIENCES, 2025)
Objective: The focus of this investigation was to examine functional recovery patterns in middle-aged individuals following arthroscopic paral meniscectomy, a minimally invasive surgical procedure involving paral excision of the knee meniscus in the early postoperative period. Methods: The current prospective interventional study was conducted at Afridi Medical Complex and Teaching Hospital, Peshawar, from August 2023 to July 2024, including 87 patients with knee meniscal tears who underwent arthroscopic partial meniscectomy. Visual Analogue Scale score and Lysholm Knee Functional Score were used to evaluate improvement postoperatively, pain, and the functional outcome, respectively. Data analysis was done through Excel software version 2003. Results: The VAS score for knee pain improved from 7.023±0.816 preoperatively to 2.518±1.065 at 12th weeks postoperatively (p-value < .001). Lysholm knee score for functional outcomes improved from 48.41±6.327 preoperatively to 81.8±10 at 12th week postoperatively (p-value < .001). Functional outcome of partial meniscectomy was excellent, good, fair, and poor outcomes were noted in 9.42%, 60%, 20%, and 10.59% of patients, respectively. Gender, BMI status, and type of meniscal tears had no effect on the functional outcome of partial meniscectomy for meniscal tears. Conclusion: Meniscal tears in adults afflict the male gender more than the female gender, and they are more likely to be degenerative than traumatic. Most of the patients had less knee discomfort at 12 weeks after an arthroscopic partial meniscectomy. At 12 weeks, over fifty percent of the patients demonstrated better short-term functional results following arthroscopic partial meniscectomy. Gender, body mass index, and meniscal tear type had no significant impact on outcome.